Antioxidant non-fluorine ion exchange membrane, preparation method and application of antioxidant non-fluorine ion exchange membrane in functional membrane

CN119823430AActive Publication Date: 2025-04-15JILIN UNIVERSITY

Patent Information

Application Number
CN202510013726.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15
Estimated Expiration
2045-01-06

Smart Images

  • Figure CN119823430A_ABST
    Figure CN119823430A_ABST
Patent Text Reader

Abstract

The invention discloses an antioxidant non-fluorine ion exchange membrane, a preparation method and application of the antioxidant non-fluorine ion exchange membrane in a functional membrane, and belongs to the technical field of functional polymer materials. The preparation method comprises the following steps: by taking N-phenyl (4, 4 '-dichlorodiphenyl) ketimine and a sodium sulfonate monomer as raw materials, carrying out Yamamoto coupling homopolymerization to prepare a polyarone precursor polymer containing Schiff base; the preparation method comprises the following steps: dissolving a polyarone precursor polymer, casting to form a membrane, and carrying out hydrolysis reaction in an acidic environment to prepare a polyarone ion exchange membrane, namely the antioxidant non-fluorine ion exchange membrane material. The antioxidant non-fluorine ion exchange membrane material has the advantages of excellent antioxidant stability, good dimensional stability, solution processability and the like, and can be applied to the fields of functional membranes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymer materials, and in particular relates to an anti-oxidation non-fluorine ion exchange membrane, a preparation method and application thereof in functional membranes. Background Art

[0002] Sulfonated polyaryletherketone materials are high-performance polymer materials with low cost, high efficiency ion exchange capacity, good mechanical properties, high thermal stability, low fuel permeability and processability. They can be widely used in fuel cells, water treatment, biomedicine, composite materials and other fields. As the most promising proton exchange membrane material to replace perfluorosulfonic acid polymers, they still have poor antioxidant stability and the difficulty in balancing proton conductivity and dimensional stability, so they are subject to certain restrictions in the application of fuel cells.

[0003] Sulfonated polyaryletherketone materials have poor antioxidant stability as proton exchange membranes (PEMs) due to the presence of ether bonds. In order to improve the antioxidant stability of PEMs, we designed a sulfonated polyaryletherketone polymer without an ether bond structure. This polymer has good film-forming properties and has high antioxidant stability and dimensional stability compared to sulfonated polyaryletherketone materials, making it an ideal material for PEMs. Summary of the invention

[0004] The purpose of the present invention is to design an antioxidant non-fluorine ion exchange membrane, a preparation method and its application in functional membranes based on molecular structure. The present invention uses N-phenyl (4,4'-dichlorodiphenyl) ketone imine and sodium sulfonate monomers as raw materials, and prepares a polyaryl ketone precursor polymer containing Schiff base through Yamamoto coupling homopolymerization; after the polyaryl ketone precursor polymer is dissolved and cast into a membrane, a polyaryl ketone ion exchange membrane, that is, an antioxidant non-fluorine ion exchange membrane material, is prepared through a hydrolysis reaction in an acidic environment. The antioxidant non-fluorine ion exchange membrane has the advantages of excellent antioxidant stability, good dimensional stability and solution processability, and can be applied to functional membranes and other fields.

[0005] The novel antioxidant non-fluorine ion exchange membrane of the present invention has a structural formula as shown in (I):

[0006]

[0007] In formula (I), A is

[0008] x and y represent the molar ratio of each component in the polymer chain, x+y=1, wherein 0<x<1.

[0009] The preparation method of a novel anti-oxidation non-fluorine ion exchange membrane described in the present invention comprises the following steps:

[0010] (1) Preparation of sodium (2,5-dichlorobenzoyl)benzenesulfonate monomer (see file: SG Jo, T H Kim, S J Yoon, SG Oh, MS Cha, HY Shin, J M Ahn, J Y Lee, Y T Hong, Synthesis and investigation of random-structured ionomers with highly sulfonated multi-phenyl pendants for electrochemical applications, Journal of Membrane Science 510 (2016) 326-337. https: / / doi.org / 10.1016 / j.memsci.2016.03.018):

[0011] Under N2 protection, 1 g of 2,5-dichlorobenzoic acid solid and 2-3 mL of thionyl chloride were added to a two-necked flask, and then 0.2-0.5 mL of pyridine was added dropwise, and the mixture was heated under reflux at 60-80°C for 3-5 hours, and the reaction system changed from a white turbid liquid to a clear transparent solution; the excess thionyl chloride solvent was then removed by reduced pressure distillation to obtain a colorless transparent solution, and after cooling, a white 2,5-dichlorobenzoyl chloride solid was obtained;

[0012] Under the protection of N2, add 2,5-dichlorobenzoyl chloride solid into a two-necked flask, add 2-3 mL of benzene as a solvent to 1 g of 2,5-dichlorobenzoyl chloride, then add anhydrous aluminum chloride solid, the molar ratio of 2,5-dichlorobenzoyl chloride to anhydrous aluminum chloride is 1:1-1.5, heat and reflux at 60-70°C for 5-7 hours, and the reaction system changes from a colorless and transparent solution to a bright yellow color; after the reaction is completed, pour the solution into a 1-4 M glacial hydrochloric acid aqueous solution, wash the organic phase after separation with a 1-5 M NaOH solution and ultrapure water respectively until it is neutral, remove excess benzene by vacuum distillation, and recrystallize the obtained crude product with petroleum ether 2-3 times to obtain white 2,5-dichlorobenzophenone crystals;

[0013] Under N2 protection, 1 g of 2,5-dichlorobenzophenone solid and 1.5-3 mL of fuming sulfuric acid with a SO3 mass content of 20% were added to a two-necked flask, and the mixture was reacted at 80-100°C for 8-16 hours. After the reaction, the mixture was poured into ice-cold ultrapure water, and a 3-5 M NaOH solution was added dropwise until a large amount of white precipitate was precipitated. The solution was filtered to obtain a crude product. The crude product was recrystallized with ultrapure water for 2-3 times to obtain a white sodium (2,5-dichlorobenzoyl) benzene sulfonate monomer, and its reaction structure is shown below:

[0014]

[0015] (2) Preparation of sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonate monomer (JP 2006-298794A, Aromatic sulfonic acid derivatives, polymers containing them, and solid polymer electrolytes and proton conducting membranes containing them):

[0016] Under N2 protection, the 2,5-dichlorobenzoyl chloride solid synthesized in step (1), biphenyl and anhydrous aluminum chloride solid are added to a two-necked flask in a molar ratio of 1:1-1.2:1-1.5, chloroform is added as a reaction solvent, and the mixture is heated to reflux at 70-80°C for 4-6 hours, wherein the reaction system is always a dark purple solution; after the reaction, the solution is poured into a 1-4M glacial hydrochloric acid aqueous solution, and after separation, the organic phase is washed with a 1-5M NaOH solution and ultrapure water until neutral, and the chloroform is removed by vacuum rotary evaporation. The obtained crude product is recrystallized with petroleum ether for 2-3 times to obtain a [1,1'-biphenyl]-4-yl (2,5-dichlorophenyl) ketone monomer as white crystals;

[0017] Under N2 protection, 1 g of [1,1'-biphenyl]-4-yl (2,5-dichlorophenyl) ketone monomer and 1.5-3 mL of fuming sulfuric acid with a SO3 mass content of 20% are added to a two-necked flask, and the mixture is reacted at 80-100°C for 8-16 hours. After the reaction is completed, the mixture is poured into ice-cold ultrapure water, and a 3-5 M NaOH solution is added dropwise until a large amount of white precipitate is precipitated. The solution is filtered to obtain a crude product. The crude product is recrystallized with ultrapure water for 2-3 times to obtain a white 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonic acid sodium monomer, and its reaction structure is shown below:

[0018]

[0019] (3) Preparation of polyaryl ketone precursor polymer:

[0020] N-phenyl (4,4'-dichlorodiphenyl) ketimine, sodium (2,5-dichlorobenzoyl) benzenesulfonate monomer prepared in step (1) or sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonate monomer prepared in step (2), 2,2'-bipyridine and anhydrous potassium carbonate were added to a dry two-necked flask, and N2 was continuously introduced. 0.5 to 2h, add anhydrous N,N-dimethylacetamide (DMAC), N,N'-dimethylformamide (DMF), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO) etc. as solvent into the flask through a syringe; after heating to 70 to 90°C, add bis(1,5-cyclooctadiene) nickel as catalyst, and keep the temperature to react for 4 to 8h; wherein the molar ratio of the total amount of N-phenyl(4,4'-dichlorodiphenyl)ketone imine and sodium sulfonate monomer to the bis(1,5-cyclooctadiene) nickel catalyst is 1:1 to 4, and the amount of N-phenyl(4,4'-dichlorodiphenyl)ketone imine monomer is not 0; bis(1,5 The molar ratio of the amount of cyclooctadiene) nickel catalyst and 2,2'-bipyridine is 1:1-3, and the mass of the solvent is 2-10 times the total mass of the reactants; after the reaction is completed and cooled to room temperature, the reaction mixture is discharged into anhydrous ethanol, and the obtained product is washed with anhydrous ethanol and ultrapure water for 5-6 times respectively, and finally vacuum dried at 50-70°C to obtain a crude product of a polyaryl ketone precursor polymer; the crude product is then dissolved with 5-10 mL of NMP solvent, insoluble impurities are removed by sand core filtration, and the polyaryl ketone precursor polymer is obtained after drying at 70-100°C to remove the solvent, and the yield is 60-80%; the reaction formula and product structure are shown as follows:

[0021]

[0022] A is independently selected from

[0023] (4) Preparation of polyaryl ketone polymer:

[0024] The polyaryl ketone precursor polymer prepared in step (3) is placed in a 0.5-2.0M acid solution (sulfuric acid or hydrochloric acid solution), and soaked at 70-100°C for 8-15h. The polymer obtained after filtration is washed with ultrapure water to a pH of 6.5-8.5, and then vacuum dried at 70-90°C to obtain a polyaryl ketone polymer. The reaction formula and product structure are shown below:

[0025]

[0026] A is independently selected from

[0027] x and y represent the molar ratio of each component in the polymer chain, x+y=1, and 0<x<1;

[0028] (5) Preparation of homogeneous film of polyaryl ketone precursor:

[0029] Dissolve 0.2-0.5 g of the polyaryl ketone precursor polymer prepared in step (3) in 5-10 mL of NMP, DMSO, DMF or DMAC solvent, completely dissolve and filter with a sand core, then cast on a glass plate, and then dry at 75-85° C. and 95-120° C. for 20-30 h to remove the solvent, to obtain a polyaryl ketone precursor homogeneous film with a thickness of 10-60 μm;

[0030] (6) Preparation of polyaryl ketone ion exchange membrane:

[0031] The polyaryl ketone precursor homogeneous film prepared in step (5) is placed in a 0.5-2.0M acid solution, soaked at 70-90°C for 8-15h, then washed with ultrapure water until the pH value is 6.5-8.5, and then dried at 70-90°C under vacuum for 10-15h to obtain a polyaryl ketone ion exchange membrane, i.e., an antioxidant non-fluoride ion exchange membrane, with a membrane thickness of 10-60μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the nuclear magnetic resonance hydrogen spectrum of the sodium (2,5-dichlorobenzoyl)benzenesulfonate monomer prepared in Example 1 (the nuclear magnetic resonance reagent is deuterated DMSO); as shown in the figure analysis, the peak shift analysis shows that the monomer has been successfully prepared;

[0033] Figure 2 This is the H NMR spectrum of the sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonate monomer prepared in Example 2 (the NMR reagent is deuterated DMSO); as shown in the figure analysis, the peak shift analysis shows that the monomer has been successfully prepared;

[0034] Figure 3 is the infrared spectrum of the polyaryl ketone precursor polymer 1 (x=45%) prepared in Example 3; at 1032 cm -1 and 1068cm -1 The characteristic absorption peak of the sulfonic acid group appeared at 1661cm -1 The carbonyl characteristic absorption peak appeared at , proving the successful coupling reaction and indicating that the polyaryl ketone precursor polymer was successfully prepared.

[0035] Figure 4 is the infrared spectrum of the polyaryl ketone precursor polymer II (x=45%) prepared in Example 6; at 1033 cm -1 and 1071cm -1 The characteristic absorption peak of the sulfonic acid group appeared at 1643 cm -1The carbonyl characteristic absorption peak appeared at , proving the successful coupling reaction, indicating that the polyaryl ketone precursor polymer II (x = 45%) was successfully prepared;

[0036] Figure 5 is the infrared spectrum of the polyaryl ketone polymer 1 (x=45%) prepared in Example 9; at 1032 cm -1 and 1067cm -1 The characteristic absorption peak of the sulfonic acid group appeared at 1651 cm -1 The carbonyl characteristic absorption peak appeared at Figure 3 , the characteristic absorption peak of carbonyl group was significantly enhanced, which proved the successful progress of hydrolysis reaction and indicated that the polyaryl ketone polymer (x = 45%) was successfully prepared;

[0037] Figure 6 is the infrared spectrum of the polyaryl ketone polymer II (x=45%) prepared in Example 10; at 1033 cm -1 and 1072cm -1 The characteristic absorption peak of the sulfonic acid group appeared at 1650cm -1 The carbonyl characteristic absorption peak appeared at Figure 4 , the characteristic absorption peak of carbonyl group was significantly enhanced, which proved the successful progress of hydrolysis reaction and indicated that the polyaryl ketone polymer II was successfully prepared;

[0038] Figure 7 These are actual photos of the polyaryl ketone precursor homogeneous membrane prepared in Example 11 and the polyaryl ketone ion exchange membrane prepared in Example 12. Figure 7 a is a homogeneous film of polyaryl ketone precursor (x = 45%), Figure 7 b is the homogeneous film 2 of polyaryl ketone precursor (x=45%), Figure 7 c is a polyaryl ketone ion exchange membrane (x = 45%), Figure 7 d is polyaryl ketone ion exchange membrane 2 (x=45%). The results show that the polymer prepared by the present invention can form a membrane, which is different from the phenomenon that the general polyaryl ketone is insoluble in common organic solvents and cannot form a membrane. DETAILED DESCRIPTION

[0039] Example 1

[0040] Preparation of 2,5-dichlorobenzoyl chloride monomer: Under N2 protection, weigh 11.46g (0.06mol) of 2,5-dichlorobenzoic acid and place it in a 100mL two-necked flask, add a shuttle-shaped magnetic stirrer. At room temperature, use thionyl chloride as the solvent, and slowly add 30mL of thionyl chloride solution and 0.5mL of pyridine solution to the single-necked bottle. After stirring at room temperature for 10 minutes, set the temperature of the oil bath to 60°C, and reflux the condenser. At this time, the system is a white turbid liquid. After heating at 60°C for 3h, the white turbid liquid turns light yellow and transparent, indicating that the reaction is over and the heating is stopped. It is taken out after being placed at room temperature. In order to obtain pure 2,5-dichlorobenzoyl chloride monomer, we choose vacuum distillation to remove excess thionyl chloride solvent, build a vacuum distillation device, set the temperature to 90°C, and collect thionyl chloride liquid. After the solvent is evaporated, the colorless transparent liquid in the bottle is 2,5-dichlorobenzoyl chloride monomer. Due to its low melting point, it is placed in a 0°C refrigerator to obtain white 2,5-dichlorobenzoyl chloride solid. The solid crude product is filtered again to obtain white crystalline 2,5-dichlorobenzoyl chloride monomer with a yield of 90%. Its chemical structure is as follows:

[0041]

[0042] Preparation of 2,5-dichlorobenzophenone monomer. Under N2 protection, 12.57 g (0.06 mol) of 2,5-dichlorobenzoyl chloride monomer and 8.00 g (0.06 mol) of anhydrous AlCl3 solid were placed in a 100 mL two-necked flask, N2 was introduced, and 22 mL (0.24 mol) of benzene solution was slowly added to the flask at room temperature. The reaction was violent at the moment of adding benzene. The temperature of the oil bath was set to 70 ° C. When the temperature was raised to 35 ° C, the 2,5-dichlorobenzophenone monomer melted by heat, and when the temperature was raised to 50 ° C, it became a clear bright yellow solution. After heating at 70 ° C for 5 hours, the heating was stopped and the solution was taken out after being placed at room temperature. The reaction solution was poured into 100 mL (2M) of glacial hydrochloric acid aqueous solution to remove AlCl3. The white emulsion obtained by separation was dissolved with 100 mL of CHCl3. The organic phase was washed with 10% NaOH solution and deionized water until neutral. The CHCl3 solvent was removed by vacuum rotary evaporation to obtain a white solid. It was recrystallized with petroleum ether three times to obtain pure 2,5-dichlorobenzophenone monomer with a yield of 70%. Its chemical structure is as follows:

[0043]

[0044] Preparation of sodium (2,5-dichlorobenzoyl) benzenesulfonate monomer. Under N2 protection, 9.00g (0.036mol) of the synthesized 2,5-dichlorobenzophenone monomer was placed in a 100mL two-necked flask, N2 was introduced, 27mL of fuming sulfuric acid with a SO3 mass content of 20% was added, and mechanical stirring was performed. The oil bath temperature was set to 80°C, and heating was stopped after the reaction for 12 hours. After leaving at room temperature, it was poured into 200mL of ice ultrapure water, and 5M NaOH solution was added dropwise until it became weakly alkaline and then the addition was stopped. At this time, the solution released a lot of heat, and a small amount of white precipitate was precipitated. After leaving at room temperature, a large amount of white solid precipitated, and the solution was filtered to obtain a white solid crude product. The crude product was recrystallized twice with ultrapure water to obtain a white powder with a yield of 61%. Its chemical structure is as follows:

[0045]

[0046] Example 2

[0047] Preparation of [1,1'-biphenyl]-4-yl (2,5-dichlorophenyl) ketone monomer: 20.95 g (0.10 mol) of 2,5-dichlorobenzoyl chloride prepared in Example 1, 23.13 g (0.15 mol) of biphenyl and 14.67 g (0.11 mol) of anhydrous AlCl3 solid were placed in a 250 mL two-necked flask, and then 100 mL of CHCl3 was added as solvent, stirred with a magnetic stirrer, and N2 was introduced. The temperature of the oil bath was set to 70°C, condensed and refluxed, and the solution turned into a black-purple solution due to the violent reaction. After heating at 70°C for 5 hours, the heating was stopped and the solution was taken out after being placed at room temperature. The reaction solution was poured into 200 mL (2M) of glacial hydrochloric acid aqueous solution to remove AlCl3, and the organic phase obtained by separation was washed with 10% NaOH solution and deionized water until neutral, and the CHCl3 solvent was removed by vacuum rotary evaporation to obtain a white solid. The solid crude product was recrystallized three times with petroleum ether to obtain a pure [1,1'-biphenyl]-4-yl (2,5-dichlorophenyl) ketone monomer with a yield of 90.2%. Its chemical structure is as follows:

[0048]

[0049] Preparation of sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonate monomer. Take 9.00g (0.028mol) of the synthesized [1,1'-biphenyl]-4-yl (2,5-dichlorophenyl) ketone monomer and place it in a 100mL two-necked flask, pass N2, add 27mL of fuming sulfuric acid with a SO3 mass content of 20%, and stir mechanically. Set the oil bath temperature to 80℃, and stop heating after the reaction for 12h. After leaving it at room temperature, pour it into 200mL of ice water, add 5M NaOH solution until it becomes weakly alkaline and stop adding. At this time, the solution releases a lot of heat, and a small amount of white precipitate is precipitated. After leaving it at room temperature, a large amount of white solid precipitates, and the solution is filtered to obtain a white solid crude product. Recrystallize it twice with ultrapure water to obtain a white powder with a yield of 70%. Its chemical structure is as follows:

[0050]

[0051] Example 3

[0052] Preparation of polyaryl ketone precursor polymer (x = 0.45, refers to the ratio of the mole number of sulfonated monomer / (the mole number of sulfonated monomer + the mole number of N-phenyl (4,4'-dichlorodiphenyl) ketone imine) at the time of feeding): 0.19g (0.54mmol) of sodium (2,5-dichlorobenzoyl) benzene sulfonate monomer, 0.22g (0.67mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketone imine, 2,2'- Pyridine 1.13g (7.26mmol) and anhydrous potassium carbonate 0.09g (0.65mmol) were dried in a vacuum oven at 60℃ for 24h, then added to a dry 25mL two-necked flask, N2 was continuously introduced for 1h, and 5mL of anhydrous DMAC was added to the flask with a syringe as a solvent; after heating to 80℃, 1.00g (3.64mmol) of bis(1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6h. After the reaction was completed and cooled to room temperature, the reaction mixture was discharged into anhydrous ethanol, and the obtained product was washed with anhydrous ethanol and ultrapure water for 5 times, and finally vacuum dried at 60℃ to obtain a crude product of polyaryl ketone precursor polymer 1. The solid crude product was dissolved with 7mL of NMP solvent, and the insoluble impurities were removed by suction filtration with a sand core. After drying at 80℃, polyaryl ketone precursor polymer 1 was obtained with a yield of 80%. Its structural formula is as follows:

[0053]

[0054] Example 4

[0055] Preparation of polyaryl ketone precursor polymer 1 (x = 0.40): 0.17 g (0.48 mmol) of sodium (2,5-dichlorobenzoyl) benzenesulfonate monomer, 0.24 g (0.73 mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketone imine, 1.13 g (7.26 mmol) of 2,2'-bipyridine and 0.08 g (0.58 mmol) of anhydrous potassium carbonate were dried in a vacuum oven at 60°C for 24 hours, then added to a dry 25 mL two-necked flask, N2 was continuously introduced for 1 hour, and 5 mL of anhydrous DMAC was added to the flask with a syringe as a solvent; after heating to 80°C, 1.00 g (3.64 mmol) of bis (1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6 hours. After the reaction, the polymer was treated in the same manner as in Example 3, with a yield of 81%, and its structural formula is as follows:

[0056]

[0057] Example 5

[0058] Preparation of polyaryl ketone precursor polymer 1 (x = 0.35): 0.15 g (0.42 mmol) of sodium (2,5-dichlorobenzoyl) benzenesulfonate monomer, 0.26 g (0.79 mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketone imine, 1.13 g (7.26 mmol) of 2,2'-bipyridine and 0.07 g (0.50 mmol) of anhydrous potassium carbonate were dried in a vacuum oven at 60°C for 24 hours, then added to a dry 25 mL two-necked flask, N2 was continuously introduced for 1 hour, and 5 mL of anhydrous DMAC was added to the flask with a syringe as a solvent; after heating to 80°C, 1.00 g (3.64 mmol) of bis (1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6 hours. After the reaction, the polymer was treated in the same manner as in Example 3, with a yield of 83%, and its structural formula is as follows:

[0059]

[0060] Example 6

[0061] Preparation of polyaryl ketone precursor polymer di (x = 0.45): 0.29g (0.54mmol) of sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonic acid monomer, 0.22g (0.67mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketimine, 1.13g (7.26mmol) of 2,2'-bipyridine and 0.09g (0.65mmol) of anhydrous potassium carbonate were dried in a vacuum oven at 60°C for 24h, added to a dry 25mL two-necked flask, and N2 was continuously introduced for 1h. Then, 5mL of anhydrous DMAC was added to the flask with a syringe as a solvent. After heating to 80°C, 1.00g (3.64mmol) of bis(1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6h. After the reaction was completed and cooled to room temperature, the reaction mixture was discharged into anhydrous ethanol, and the obtained product was washed with anhydrous ethanol and ultrapure water for 5 times, and finally vacuum dried at 60°C to obtain a crude product of polyaryl ketone precursor polymer II. The solid crude product was dissolved with 7mL of NMP solvent, and insoluble impurities were removed by filtration with a sand core. After drying at 80°C, polyaryl ketone precursor polymer II was obtained with a yield of 79%. Its structural formula is as follows:

[0062]

[0063] Example 7

[0064] Preparation of polyaryl ketone precursor polymer di (x = 0.40): 0.25g (0.48mmol) of sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonic acid monomer, 0.19g (0.24mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketimine, 1.13g (7.26mmol) of 2,2'-bipyridine and 0.08g (0.58mmol) of anhydrous potassium carbonate were dried in a vacuum oven at 60°C for 24h, added to a dry 25mL two-necked flask, and N2 was continuously introduced for 1h. Then, 5mL of anhydrous DMAC was added to the flask with a syringe as a solvent. After the temperature was raised to 80°C, 1.00g (3.64mmol) of bis(1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6h. After the reaction, the polymer was treated in the same manner as in Example 6, with a yield of 80%. Its structural formula is as follows:

[0065]

[0066] Example 8

[0067] Preparation of polyaryl ketone precursor polymer di (x = 0.35): 0.22 g (0.42 mmol) of sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonic acid, 0.26 g (0.79 mmol) of N-phenyl (4,4'-dichlorodiphenyl) ketimine, 1.13 g (7.26 mmol) of 2,2'-bipyridine and 0.07 g (0.50 mmol) of anhydrous potassium carbonate were dried in a vacuum oven at 60°C for 24 h, added into a dry 25 mL two-necked flask, N2 was continuously introduced for 1 h, and 5 mL of anhydrous DMAC was added into the flask with a syringe as a solvent. After the temperature was raised to 80°C, 1.00 g (3.64 mmol) of bis(1,5-cyclooctadiene) nickel catalyst was added, and the temperature was maintained for 6 h. After the reaction, the polymer was treated in the same manner as in Example 6, with a yield of 82%. Its structural formula is as follows:

[0068]

[0069] Example 9

[0070] Preparation of polyaryl ketone polymer 1: 0.2 g of each polyaryl ketone precursor polymer 1 prepared in Example 3, Example 4 and Example 5 were placed in 20 mL of 1 M acid solution, respectively, and soaked in an oven at 80°C for 12 h. The filtered polymer was washed with ultrapure water to pH = 7, and dried in a vacuum oven at 80°C for 12 h to obtain three polyaryl ketone polymers 1 with different ratios, with a yield of about 95%. The structural formula is as follows:

[0071]

[0072] Example 10

[0073] Preparation of polyaryl ketone polymer II: 0.2 g of each polyaryl ketone precursor polymer II prepared in Example 6, Example 7 and Example 8 were placed in 20 mL of 1 M acid solution, respectively, and soaked in an oven at 80°C for 12 h. The filtered polymer was washed with ultrapure water to pH = 7, and dried in a vacuum oven at 80°C for 12 h to obtain three polyaryl ketone polymers II with different ratios, with a yield of about 96%. The structural formula is as follows:

[0074]

[0075] Embodiment 11

[0076] Preparation of polyaryl ketone precursor homogeneous film: 0.3 g of each of polyaryl ketone precursor polymer 1 and polyaryl ketone precursor polymer 2 prepared in Examples 3-5 and 6-8 were taken, dissolved in 7 mL of NMP solvent, filtered with a sand core to remove insoluble impurities, and then spread on a 6×6 cm glass plate by a casting method, dried at 80°C and 100°C for 24 hours, respectively, and naturally cooled to obtain two polyaryl ketone precursor homogeneous films with different ratios, and the thickness of the film was about 25 μm. The chemical structure of the polyaryl ketone precursor homogeneous film is as follows:

[0077]

[0078] A is independently selected from

[0079] Example 12

[0080] Preparation of polyarylketone ion exchange membrane: Take two polyarylketone precursor homogeneous membranes of different proportions prepared in Example 11 and soak them in 1M acid solution, hydrolyze them at 80°C for 12h, wash them with clean water until they are neutral, and then dry them in a vacuum oven at 80°C to obtain polyarylketone ion exchange membrane 1 and polyarylketone ion exchange membrane 2 of different proportions. The thickness of the two prepared polyarylketone ion exchange membranes is about 30μm. The chemical structure of the polyarylketone ion exchange membrane is as follows:

[0081]

[0082] A is independently selected from

[0083] Example 13

[0084] Prepare 500 mL of 2 ppm Fenton's reagent: Take 46.5 mL of 30% H2O2 and add it to ultrapure water to make 500 mL of solution, then add 1 mg of anhydrous FeSO4 and stir well.

[0085] The prepared polyaryl ketone ion exchange membranes with different proportions and SPEEK membranes with a sulfonation degree of 60% were cut into 1×1 cm size membranes for oxidation stability testing. 1-35%, 1-40% and 1-45% respectively represent the three different raw material dosage ratios of polyaryl ketone ion exchange membrane one, i.e. x=0.35, 0.40 and 0.45; 2-35%, 2-40% and 2-45% respectively represent the three different raw material dosage ratios of polyaryl ketone ion exchange membrane two, i.e. x=0.35, 0.40 and 0.45. The films were then immersed in glass bottles containing 50 mL, 2 ppm Fenton's reagent and heated in an oven at 80°C. The mass retention rate wt% of the film after immersion for 1 hour was recorded [After 1 hour of oxidation stability test, the ratio of the remaining mass of the film (W2) to the mass of the film before the test (W1) is the mass retention rate wt%, i.e. the mass retention rate 】 and the time t until the film is damaged. Three groups of parallel experiments were carried out for each ratio of membrane. The experimental results are shown in Table 1.

[0086] Table 1: Data on the mass retention rate (wt%) and the time t until damage after the film was immersed for 1 hour

[0087] SPEEK 1-35% 1-40% 1-45% 2-35% 2-40% 2-45% t / h 1.0 65.0 60.5 53.0 60.0 52.0 45.0 wt% 80.1 99.4 98.9 98.5 99.1 98.5 98.1

[0088] The results in Table 1 show that, compared with the SPEEK membrane, the polyaryl ketone ion exchange membrane prepared in the present invention has excellent anti-oxidation stability.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an antioxidant non-fluorine ion exchange membrane, the steps of which are as follows: (1) Preparation of polyaryl ketone precursor polymer: N-phenyl (4,4'-dichlorodiphenyl) ketimine, sodium (2,5-dichlorobenzoyl) benzenesulfonate monomer or sodium 4-(2,5-dichlorobenzoyl)-[1,1'-biphenyl]-2,4'-disulfonate monomer, 2,2'-bipyridine and anhydrous potassium carbonate were added to a dry two-necked flask and N2 was continuously introduced. 0.5 to 2h, add the solvent to the flask with a syringe; after heating to 70 to 90°C, add bis(1,5-cyclooctadiene) nickel as a catalyst, and maintain the temperature for 4 to 8h; wherein the molar ratio of the total amount of N-phenyl(4,4'-dichlorodiphenyl)ketone imine and sodium sulfonate monomers to the bis(1,5-cyclooctadiene) nickel catalyst is 1:1 to 4, and the amount of N-phenyl(4,4'-dichlorodiphenyl)ketone imine monomer is not 0; the molar ratio of the amount of bis(1,5-cyclooctadiene) nickel catalyst to 2,2'-bipyridine is 1:1 to 3 , the mass of the solvent is 2 to 10 times the total mass of the reactants; after the reaction is completed and cooled to room temperature, the reaction mixture is discharged into anhydrous ethanol, the obtained product is washed 5 to 6 times with anhydrous ethanol and ultrapure water respectively, and finally vacuum dried at 50 to 70°C to obtain a crude polyaryl ketone precursor polymer; the crude product is then dissolved with 5 to 10 mL of NMP solvent, insoluble impurities are removed by filtration with a sand core, and the polyaryl ketone precursor polymer is obtained after drying at 70 to 100°C to remove the solvent, with a yield of 60 to 80%; the product structure is shown below: A is independently selected from (2) 0.2-0.5 g of the polyaryl ketone precursor polymer prepared in step (1) is dissolved in 5-10 mL of solvent, completely dissolved, filtered with a sand core, and cast on a glass plate, and then dried at 75-85° C. and 95-120° C. for 20-30 h to remove the solvent, to obtain a polyaryl ketone precursor homogeneous film having a thickness of 10-60 μm; (3) placing the polyaryl ketone precursor homogeneous membrane prepared in step (2) in a 0.5-2.0M hydrochloric acid solution, soaking it at 70-90°C for 8-15h, then washing it with ultrapure water until the pH value is 6.5-8.5, and then drying it at 70-90°C under vacuum for 10-15h to obtain a polyaryl ketone ion exchange membrane, i.e., an antioxidant non-fluorine ion exchange membrane, having a membrane thickness of 10-60μm.

2. The method for preparing an antioxidant non-fluorine ion exchange membrane according to claim 1, characterized in that: The solvent in step (1) and step (2) is anhydrous N,N-dimethylacetamide, N,N'-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

3. An antioxidant non-fluorine ion exchange membrane, characterized in that: The method is prepared by the method of claim 1 or 2.

4. Use of the antioxidant non-fluorine ion exchange membrane according to claim 3 in functional membranes.

5. A polyaryl ketone polymer, the structure of which is shown below: A is independently selected from x and y represent the molar ratio of each component in the polymer chain, x+y=1, and 0<x<1.

6. The method for preparing a polyaryl ketone polymer according to claim 5, characterized in that: The polyaryl ketone precursor polymer prepared in step (1) of claim 1 is placed in a 0.5-2.0M acid solution and soaked at 70-100°C for 8-15h. The polymer obtained after filtration is washed with ultrapure water to a pH of 6.5-8.5, and then vacuum dried at 70-90°C to obtain a polyaryl ketone polymer.

7. The method for preparing a polyaryl ketone polymer according to claim 6, characterized in that: The acid solution is a sulfuric acid solution or a hydrochloric acid solution.

Citation Information

Patent Citations

  • Aromatic sulfonic acid derivative, sulfonated polymer, solid polyelectrolyte, and proton-conductive film

    JP2006298794A

  • Sulfonated polyarone polymer and preparation method thereof

    CN118126295A

  • Cross-linked poly(arylene ether ketone) with sulfonated back bone, polymer electrolyte membrane for fuel cell prepared therewith and prepartion method thereof

    KR1020130098512A

  • Method of making polyarylene ionomers and membranes

    US20120289678A1

  • Sulfonated benzene polyphenyl ionomer and method for preparing same, and proton exchange membrane

    WO2023185149A1

Cited By

  • Polyaryletherketone resin, preparation method and application of polyaryletherketone resin in functional film

    CN120842555A

  • A polyaryletherketone resin, a preparation method and application thereof in functional films

    CN120842555B